A diamondoid net sustained by halogen bonds: employing a cyclobutane to generate a tetrahedral architecture. Issue 26 (20th May 2020) - Oburn, Shalisa M.; Santana, Carlos L.; Elacqua, Elizabeth; Groeneman, Ryan H.
Abstract : A purely organic dia net sustained by halogen bonds that contains nodes comprised of rctt -tetrakis (4-pyridyl) cyclobutane, obtained from a solid-state photoreaction, is reported. Abstract : A halogen-bonded eight-fold interpenetrated diamondoid net was constructed employing a node generated in the solid state. Specifically, co-crystallization of a tetrahedral-like tecton, rctt -tetrakis(4-pyridyl)cyclobutane (4, 4′-TPCB), combined with a rigid halogen-bond donor, 1, 4-diiodoperchlorobenzene, achieved a diamondoid architecture. In the co-crystal, 4, 4′-TPCB is found to form three types of linkages based on one cis - and two trans -orientations enabled by the intrinsic rctt -stereochemisty of the central cyclobutane ring. Thus, 4, 4′-TPCB is able to adapt to the constraints of the diamondoid net owing to the flexibility of the pendant 4-pyridyl groups.